"Oh the weather outside is frightful": Severe injury secondary to falls while installing residential Christmas lights. Issue 1 (January 2016) - Driedger, Michael R.; Gupta, Arjun; Wells, Bryan; Dixon, Elijah; Ball, Chad G.
Abstract: Introduction: Falls are an increasingly common source of severe traumatic injury. They now account for approximately 40% of both overall trauma volumes and injury-related deaths within Canada. In northern climates, the risk of all types of falls may increase during the fall/winter months when conditions become increasingly dangerous. The purpose of this study was to define the injury and patient demographics of severe trauma that occurs during falls associated with the installation of Christmas lights. Patients and methods: All patients who were admitted to a referral level 1 trauma center (2002–2012) with severe injuries (ISS ≥ 12) caused during Christmas light installation were retrospectively reviewed. Standard statistical methodology was utilised ( p  < 0.05 = significant). Results: A total of 40 patients were severely injured (95% male; mean age = 55 years; mean ISS = 25.7 (range: 12–75)) while installing Christmas lights. Injuries included: neurologic (68%), thoracic (68%), spinal (43%), extremity (40%), and multiple other sites. Fall mechanisms were: ladder (65%), roof (30%), ground (3%) and railing (3%). Interventions included intubation and critical care (20%), as well as orthopaedic and neurosurgical operative repairs (30%). The median length of hospital stay was 15.6 days (range: 2–165). The fall-related morbidity (28%) and mortality (5%) were significant with a total of 12.5% patients requiring transfer to a long-term care or rehabilitation facility. Conclusions: Falls while installing Christmas lights during the fall/winter seasons can result in severe life-altering injuries with considerable morbidity and mortality. Caution should be employed when installing lights at any height.